2012
DOI: 10.1287/orsc.1110.0661
|View full text |Cite
|
Sign up to set email alerts
|

Knowing Where You Stand: Physical Isolation, Perceived Respect, and Organizational Identification Among Virtual Employees

Abstract: T his research investigates the relationship between virtual employees' degree of physical isolation and their perceived respect in the organization. Respect is an identity-based status perception that reflects the extent to which one is included and valued as a member of the organization. We hypothesize that the degree of physical isolation is negatively associated with virtual employees' perceived respect and that this relationship explains the lower organizational identification among more physically isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
234
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(263 citation statements)
references
References 55 publications
5
234
0
1
Order By: Relevance
“…And subordinates with managers who worked remotely reported more negative work experiences compared to those with colocated managers (Golden & Fromen 2011). The physical isolation that can come with working remotely is correlated with feeling less respected by the organization, which weakens organizational identification (Bartel et al 2012). A meta-analysis found that telecommuting can increase work-family conflict due to longer hours (Allen et al 2015) and because it blurs the boundaries between work and family roles (e.g., Schieman & Young 2010, Allen & Shockley 2009, Kossek & Michel 2011.…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
See 1 more Smart Citation
“…And subordinates with managers who worked remotely reported more negative work experiences compared to those with colocated managers (Golden & Fromen 2011). The physical isolation that can come with working remotely is correlated with feeling less respected by the organization, which weakens organizational identification (Bartel et al 2012). A meta-analysis found that telecommuting can increase work-family conflict due to longer hours (Allen et al 2015) and because it blurs the boundaries between work and family roles (e.g., Schieman & Young 2010, Allen & Shockley 2009, Kossek & Michel 2011.…”
Section: Flexibility In Where Work Is Accomplishedmentioning
confidence: 99%
“…Those in alternative work arrangements may experience more ambiguity around professional affiliations and identities (Dibble & Gibson 2012) and lack the ability to personalize their spaces with identity markers (Byron & Laurence 2015). Working remotely can also weaken one's organizational or communal identification with coworkers (Bartel et al 2012). Future research should further explore how alternative work arrangements influence worker identification with their organizations and professions, and how organizations might work to strengthen employee identification without threatening their desired flexibility and autonomy.…”
Section: Creating a More Positive New World Of Workmentioning
confidence: 99%
“…In the current study respect was defined as 'an identity-based status perception that reflects the extent to which one is included and valued as a member of the organization' (Bartel, Wrzesniewski & Wiesenfeld, 2012 were adjusted to change perspective from the self ('I') to another person ('Tom'). An example item was "I believe Tom has a good reputation in the organization".…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Of particular relevance, recent research examining the identity formation of remote workers suggests that extreme isolation can hamper individuals' progress toward constructing a social identity, hindering the remote employees' ability to see the self as a coherent part of the broader organization, and effectively stifling the internalization of organizational motives (Bartel et al, 2007;Bartel, Wrzesniewski, and Wiesenfeld, 2012). This social isolation, and the resultant stifling of social identity formation, tends to reduce individuals' motivation to act to the benefit of other in-group members (e.g.…”
Section: Seeking To Belong At Work 12mentioning
confidence: 99%